The Effect Of Non Performing Loan (NPL) On Earning Per share (EPS), Return On Investment (ROI), And Rate Of Return (ROR) In BUMN Banks Listed On The Indonesia Stock Exchange (IDX) From 2013-2022 - Ulima Nathania Tamba, Devina; Benny Alexandri, Mohammad; Fauzan, Farisadri (DINASTI RESEARCH, 2024)
The aim of this research is to determine the effect of Non-Performing Loans (NPL) on Earning Per Share (EPS), Return on Investment (ROI), and Rate of Return (ROR) in state-owned banks listed on the Indonesia Stock Exchange (BEI) for the period 2013- 2022. Researchers used quantitative research methods with samples in the research, namely four state-owned banks listed on the BE, using SEM (Structural Equation Modeling) and the Partial Least Square (PLS) approach as methods in the research process. Research findings show that Non Performing Loans (NPL) have a significant effect on Earning Per Share (EPS), Non Performing Loans (NPL) have a significant effect on Return On Investment (ROI), and Non Performing Loans (NPL) have a significant effect on the Rate of Return ( ROR) BUMN Bank for the 2013-2022 period with testing using a significance level of 5%. Apart from that, research findings also show that the Covid pandemic has had a negative impact on the NPL, EPS, ROI and ROR ratios as evidenced by the ratio values ??being low and decreasing very significantly in the 2020-2021 period. Of the three ratios used, the Return On Investment (ROI) ratio is the ratio that is most influenced by NPL (Non Performing Loan), and conversely the one that is least influenced by NPL (Non Performing Loan) is the Rate of Return (ROR) ratio.